2014
DOI: 10.1371/journal.pone.0092181
|View full text |Cite
|
Sign up to set email alerts
|

Functional Studies of p.R132C, p.R149C, p.M283V, p.E431K, and a Novel c.652-2A>G Mutations of the CYP21A2 Gene

Abstract: Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency is the most frequent inborn error of metabolism and accounts for 90–95% of CAH cases. In the present work, we analyzed the functional consequence of four novel previously reported point CYP21A2 mutations -p.R132C, p.R149C, p.M283V, p.E431K- found in Argentinean 21-hydroxylase deficient patients. In addition, we report an acceptor splice site novel point mutation, c.652-2A>G, found in a classical patient in compound heterozygosity with the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…On the other hand, Taboas et al recently described a patient with NC type with p.V281L/p.D322G-p. E431K, and reported that the p.E431K mutation produced about 20% residual enzyme activity and a reduced protein level of CYP21A2 [14,15]. Although their patient did not have p.E431K on single allele and had a different clinical type and combination of mutations, their presented residual enzyme activity and protein data are not consist with our patient's clinical course, or our functional analysis.…”
Section: Disclosuresmentioning
confidence: 55%
See 1 more Smart Citation
“…On the other hand, Taboas et al recently described a patient with NC type with p.V281L/p.D322G-p. E431K, and reported that the p.E431K mutation produced about 20% residual enzyme activity and a reduced protein level of CYP21A2 [14,15]. Although their patient did not have p.E431K on single allele and had a different clinical type and combination of mutations, their presented residual enzyme activity and protein data are not consist with our patient's clinical course, or our functional analysis.…”
Section: Disclosuresmentioning
confidence: 55%
“…While the IVS2-13 A/C>G mutation is known as a common mutation in patients with the SW type [12,13], p.E431K is a rare point mutation that arises independently of the pseudogene. Although Minutolo et al reported a patient with NC CAH who had p.V281L/p.D322G-p.E431K [14,15], the mutation (NM_000500.7, c. 1401 G>A) has not been reported in the literature or in the single nucleotide polymorphism (SNP) database of the dbSNP-polymorphism repository (http://www.ncbi.nlm.nih.gov/SNP/) apart from their report. This is the first report of a CYP21A2 p.E431K mutation with no accompanying mutation on the same allele.…”
Section: Missense Mutation (Ivs2-13 A/c>g and Pe431k) Of The Cyp21a2mentioning
confidence: 99%
“…To validate our method, we estimated the in silico enzymatic activity of mutants with experimental activities reported from 2014 up to the present21222324, excluding residues known to impair protein function independently of protein stability. To accomplish this, the predicted residual activity after calculation of ∆∆G was compared with the activity reported in functional assays and with the patients’ phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a leucine residue is located at this position in the mouse and the rat proteins. In addition, in vitr o studies have suggested that the presence of two mild mutations in cis is generally associated with a severe impairment of enzymatic activity23495051. However, the patient with the p.P335L variant presented a NC phenotype, carrying a large gene conversion/deletion of the CYP21A2 gene on the homologous allele (null allele) and the mild p.V281L mutation in cis.…”
Section: Discussionmentioning
confidence: 99%
“…For patients recruited until 2011, the most frequent pseudogene‐derived pathogenic variants in the CYP21A2 gene were screened by allele‐specific PCR or PCR‐RFLP, following the methodology previously established in our laboratory 19 . Samples with at least one nondetermined allele or a discordant phenotype‐genotype correlation and samples from patients recruited from 2011 to 2018 (N = 343), direct sequencing of the entire coding region and the proximal promoter of the CYP21A2 gene was performed as previously described 20,21 . In addition, the distal regulatory region, named promotor Z, 22 was also assessed in samples with the p.P483S variant as described before 23 .…”
Section: Methodsmentioning
confidence: 99%